Resisting the System: A Critical Race Theory Analysis of Racial Discrimination in Netflix’s Self Made (PANOPTICON: Journal of English Studies, 2026)
This study examines the portrayal of racial discrimination and its influence on identity formation and agency in the Netflix limited series Self Made: Inspired by the Life of Madam C.J. Walker (2020). Employing a qualitative descriptive methodology, the research investigates how protagonist Madam C.J. Walker navigates and resists systemic barriers within a racialized socioeconomic landscape. The analysis is grounded in Critical Race Theory (Delgado & Stefancic, 2001) and Mellor’s (2004) framework of responses to racism. Findings indicate that racial discrimination is depicted as a normalized element of social interaction, manifested through interpersonal belittlement and intra-racial tensions. Furthermore, the study identifies the presence of "interest convergence," wherein dominant power structures support Walker’s entrepreneurial efforts only when such support aligns with their own material or political interests. The study concludes that Self Made functions as a narrative of resilience, highlighting the necessity of multifaceted resistance strategies in the face of institutionalized racism.